2007
DOI: 10.1007/s11130-007-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High β-Glucan Barley on Serum Cholesterol Concentrations and Visceral Fat Area in Japanese Men—A Randomized, Double-blinded, Placebo-controlled Trial

Abstract: This study investigated whether the consumption of a diet in which high-beta-glucan barley replaced rice would reduce the visceral fat area as well as the serum low-density lipoprotein cholesterol (LDL-C) and total cholesterol (TC) in hypercholesterolemic Japanese men. A randomized, double-blinded, placebo-controlled intervention study was conducted in 44 hypercholesterolemic Japanese men with a body mass index (BMI) >22 kg/m2. The subjects were randomly assigned to groups consuming either rice (placebo group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 12 publications
3
65
1
6
Order By: Relevance
“…The protective effects of dietary fiber against cardiovascular disease (CVD), mediated through a reduction in serum lipids, were first reported 440 years ago by Keys et al (1960); later research led to the dietary fiber hypothesis proposed by Burkitt et al (1974) and Trowell (1975) that states that a high intake of starchy carbohydrates and fiber is protective against CVD. Many trials showed a hypocholesterolemic effect of an increased intake of fiber from cereals, such as barley, rice and oats; the active component in barley has been identified as beta-glucans, which reduces serum total cholesterol by 5-10% (according to Anderson, 1987;McIntosh et al, 1991;Shimizu et al, 2008;Talati et al, 2009) and by 20% (according to Behall et al, 2004), although not all studies (Keogh et al, 2003) showed barley beta-glucans to be hypocholesterolemic.…”
Section: Introductionmentioning
confidence: 99%
“…The protective effects of dietary fiber against cardiovascular disease (CVD), mediated through a reduction in serum lipids, were first reported 440 years ago by Keys et al (1960); later research led to the dietary fiber hypothesis proposed by Burkitt et al (1974) and Trowell (1975) that states that a high intake of starchy carbohydrates and fiber is protective against CVD. Many trials showed a hypocholesterolemic effect of an increased intake of fiber from cereals, such as barley, rice and oats; the active component in barley has been identified as beta-glucans, which reduces serum total cholesterol by 5-10% (according to Anderson, 1987;McIntosh et al, 1991;Shimizu et al, 2008;Talati et al, 2009) and by 20% (according to Behall et al, 2004), although not all studies (Keogh et al, 2003) showed barley beta-glucans to be hypocholesterolemic.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many Western countries now only use barley predominantly for animal feed and malting. However, there has been renewed interest worldwide in barley as food due to its many health benefits, including its potential in reducing the risk of cardiovascular disease via cholesterol lowering (Behall et al, 2004a, b;Keenan et al, 2007;Shimizu et al, 2008), and improvement of glucose tolerance (Pick et al, 1998;Behall et al, 2006;Hinata et al, 2007). The active ingredient thought to provide barley its health benefits is b-glucan.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of studies have been carried out to test the efficacy of barley or b-glucan derived from barley as cholesterol-lowering agents. However, some studies have demonstrated no benefits (Keogh et al, 2003;Biorklund et al, 2005), whereas others have shown reductions in plasma lipids (McIntosh et al, 1991;Li et al, 2003;Behall et al, 2004a, b;Keenan et al, 2007;Shimizu et al, 2008). The varying results in human studies may be due to factors such as dose size, food matrix, type of intervention, background diet and subjects' characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports demonstrating the beneficial physiological effects of barley on lipid metabolism in animals and humans (Oda et al, 1994;Yang et al, 2003;Ikegami et al, 1996;Behall et al, 2004;Shimizu et al, 2008). With respect to the animal experiments, many studies concerned themselves with high cholesterol and high-fat food, but few reports evaluated the long-term effect of barley on lipid metabolism in animals given a diet of ordinary nutritional composition.…”
Section: Discussionmentioning
confidence: 99%